THE FACTORS THAT INFLUENCE STUDENTS’ VIEWS ON SELF-EMPLOYMENT AMONG IKBN STUDENTS - Wan Nur Syuhada WAN ISMAIL; Shamsul Huda ABD RANI (Studia Universitatis Babeş-Bolyai Negotia, 2017)
Objective: The purpose of this paper is to examine the influence of college experience, family support and role model towards students’ views on self-employment. Methodology: A questionnaire survey was administered to 338 IKBN (Institut Kemahiran Belia Negara) students in Northern region of Malaysia. This group was selected as respondents because they were exposed to focus on technical and skills-based learning to be skills worker that can produce a product or provide a service and these will lead them to be self-employed after their graduation. This study utilize simple random sampling as a sample technique and using SPSS version 22 to analyze the data obtained. The analysis technique used are descriptive analysis, reliability, normality and regression analysis. Results: This study indirectly found that there is significant relationship between independent and dependent variables. The main finding in this study indicate that all the independent variables tested support the students’ views on self-employment. Besides that, the research also found that family support is the most influence and plays important roles in sharpen students’ views on self-employment. Implication: This research contributes to both theoretically and practically. Consistent with the Knowledge Spillover Theory of Entrepreneurship, technical knowledge has capability in sharpening views on self-employment. This knowledge rises opportunities and able to sharpen views on self-employment among students. The research findings expected that IKBN can produce more skillful of self-employments among graduate students. Thus, this can help government in controlling and reducing the unemployment rate in Malaysia.